Coexistence of Unconditionality and Conditionality of the Davidic Covenant in Chronicles1. (29th October 2012) - Hwang, Sunwoo
Abstract : The Davidic covenant is the basis of the hope for a restoration of the Davidic kingdom in Chronicles. The Chronicler's retention of both the unconditionality and conditionality of the Davidic covenant does not mean that he was inconsistent; in my view, he views the two as complementary. The royal promise is conditional in the sense that the Davidic kings are disciplined and punished, and the kingdom ceases to exist when it does not meet the conditions set down by YHWH; it is unconditional in that YHWH's will never depart from the kingdom, as seen in 1 Chron. 17:13 where YHWH distinguishes his promise to David from his promise to Saul. Following this line of thought, the Chronicler yearns for further change in the postexilic temple‐centered society through a restoration of the lost kingdom by appealing to the Davidic covenant. The latter subtends the preservation of the Davidic kingdom in the preexilic period and a possible restoration in the postexilic period.